Performance Comparison Between Balloon Active Contour and Seed Based Region Growing Methods in Segmenting Breast Ultrasound Images - Abdul Malek, Aminah; Mohamed, Norlyda; Nadiah Muhammad, Nurul; Adillah Muhammad Nahar, Shaffiqah; Khadijah Mohd Asri, Siti (International Journal of Engineering and Technology, 2018)
Segmentation images have been widely used in the medical field, especially in detecting breast cancer. Ultrasound images can be used as modalities in early detection of breast cancer. However, the detection becomes difficult due to speckle noise and unwanted information in the ultrasound images. In this study, performance comparison between Balloon Active Contour (BAC) and Seed-Based Region Growing (SBRG) methods in segmenting breast ultrasound images was carried out. The performance of segmentation results for both methods was measured in terms of accuracy and sensitivity. Results obtained showed that the accuracy for SBRG and BAC methods was 90.55% and 87.41%, respectively. In addition, sensitivity for both methods was 83.3 and 79.0, respectively. This implies that the SBRG method has better performance compared to the BAC method in segmenting breast cancer in ultrasound images. Â